Bariatric surgery induces pancreatic cell transdifferentiation as indicated by single‐cell transcriptomics in Zucker diabetic rats - Liang, Yongjun; Widjaja, Jason; Sun, Jiawei; Li, Mengyi; Qiao, Zhengdong; Cao, Ting; Wang, Yueqian; Zhang, Xiong; Zhang, Zhongtao; Gu, Yan; Zhang, Peng; Yang, Jianjun (Journal of diabetes, 2024)
Aims Bariatric surgery results in rapid recovery of glucose control in subjects with type 2 diabetes mellitus. However, the underlying mechanisms are still largely unknown. The present study aims to clarify how bariatric surgery modifies pancreatic cell subgroup differentiation and transformation in the single‐cell RNA level. Methods Male, 8‐week‐old Zucker diabetic fatty (ZDF) rats with obesity and diabetes phenotypes were randomized into sleeve gastrectomy (Sleeve, n = 9), Roux‐en‐Y gastric bypass (RYGB, n = 9), and Sham (n = 7) groups. Two weeks after surgery, the pancreas specimen was further analyzed using single‐cell RNA‐sequencing technique. Results Two weeks after surgery, compared to the Sham group, the metabolic parameters including fasting plasma glucose, plasma insulin, and oral glucose tolerance test values were dramatically improved after RYGB and Sleeve procedures (p < .05) as predicted. In addition, RYGB and Sleeve groups increased the proportion of pancreatic β cells and reduced the ratio of α cells. Two multiple hormone‐expressing cells were identified, the Gcg+/Ppy + and Ins+/Gcg+/Ppy + cells. The pancreatic Ins+/Gcg+/Ppy + cells were defined for the first time, and further investigation indicates similarities with α and β cells, with unique gene expression patterns, which implies that pancreatic cell transdifferentiation occurs following bariatric surgery. Conclusions For the first time, using the single‐cell transcriptome map of ZDF rats, we reported a comprehensive characterization of the heterogeneity and differentiation of pancreatic endocrinal cells after bariatric surgery, which may contribute to the underlying mechanisms. Further studies will be needed to elucidate these results. Highlights The single‐cell transcriptome map of Zucker diabetic fatty rats' pancreatic endocrine cells after bariatric surgery were reported for the first time. An increased ratio of pancreatic β cells, which is associated with other pancreatic endocrine cell types transdifferentiated into β cells, was observed following bariatric surgery. For the first time, we identify the elevation of cells in the pancreas following bariatric surgery, which is indirect evidence to support the existence of transdifferentiation.